Criteria of project success: An exploratory re-examination. - Mohamed, Mohd Zain; Lim, C.S. (Elsevier, 1999)
Doubts often arise about what and who actually determine project success. The purpose of this article is to explore the issues from different perspectives of people looking at the project. The difference between criterion and factor is first discussed. Criteria are the set of principles or standards by which judgement is made; whereas factors are the set of circumstances, facts, or influences which contribute to the result. This article then proposes to classify project success into two categories: the macro and micro viewpoints. Some pictorial representations and models are presented to assist in the understanding of the concepts. It is suggested that two criteria are sufficient to determine the macro viewpoint of project success: completion and satisfaction. Whereas the completion criterion alone is enough to determine the micro viewpoint of project success.